2017
DOI: 10.4081/vsd.2017.6335
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of two dogs after mitral valve plasty

Abstract: Two small 9-year-old dogs received mitral valve plasty (MVP) for severe mitral regurgitation that could not be controlled via drug administration. MVP consisted of chordal reconstruction using expanded polytetrafluoroethylene (ePTFE) sutures and semicircular suture annuloplasty using polypropylene sutures. In both cases, the clinical signs dramatically improved after MVP, although postoperative echocardiography revealed slight residual mitral regurgitant flow. Both dogs survived for several years after MVP wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Most recently, a long-term clinical report shows good results with ePTFE sutures in 2 small dogs, which survived for approximately 9 years after the MVP operation. 17 In the current study, each ePTFE suture was covered with endocardial tissue from both the papillary muscle and anterior leaflet sides from 1.5 months after the operation, and each ePTFE suture was completely covered by a tissue sheath and appeared like a native chorda from 2 months after the operation in the shortterm group. In the long-term group, the ePTFE suture showed no changes in thickness or flexibility 12 months after the operation and appeared like a native chorda, as reported in sheep.…”
Section: Discussionmentioning
confidence: 80%
“…Most recently, a long-term clinical report shows good results with ePTFE sutures in 2 small dogs, which survived for approximately 9 years after the MVP operation. 17 In the current study, each ePTFE suture was covered with endocardial tissue from both the papillary muscle and anterior leaflet sides from 1.5 months after the operation, and each ePTFE suture was completely covered by a tissue sheath and appeared like a native chorda from 2 months after the operation in the shortterm group. In the long-term group, the ePTFE suture showed no changes in thickness or flexibility 12 months after the operation and appeared like a native chorda, as reported in sheep.…”
Section: Discussionmentioning
confidence: 80%
“…Discussion There are three main techniques of MVP: (1) CR for ruptured or elongated chordae tendineae, (2) AP for a dilated mitral annulus to increase the coaptation area of the AL and PL, and (3) VP for deformed or redundant valve leaflets (Carpentier et al, 1971). To treat severe MR caused by ruptured chordae of the AL, Kanemoto et al (2017) reported the use of a basic MVP technique that combined CR using ePTFE sutures for the AL and semicircular suture AP using polypropylene sutures for the dilated mitral annulus. However, in a severe case of MR complicated by the presence of multiple lesions in both leaflets, two additional techniques are required: valve scallop suture VP for the PL and anterior commissure AP (the Kay method) (Kay and Egerton, 1963).…”
Section: Postoperative Coursementioning
confidence: 99%
“…Recently, there have been increased reports of using MVP to treat MR in dogs (Kanemoto et al, 1990(Kanemoto et al, , 2004Boggs et al, 1996;Griffiths et al, 2004;Uechi, 2012). However, there have been few reports of the application of MVP to treat severe MR involving the posterior leaflet (PL) in small dogs (Boggs et al, 1996;Uechi, 2012;Kanemoto et al, 2017), in whom MVR was previously indicated (Orton et al, 2005;Taguchi et al, 2014). Herein, we describe a case of severe MR caused by multiple lesions in the PL in a mixed Chihuahua, who was treated with a combination of the following three MVP techniques: artificial chordal reconstruction (CR) for the anterior leaflet (AL) and the PL, semicircular suture annuloplasty (AP) for a dilated mitral annulus, and valvuloplasty (VP) using newly devised direct scallop sutures for the PL.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-circular suture annuloplasty (SAP) (modified DeVega) method: in this technique, alternatively, purse-string suture with proline suture attaches the two pledgets around half the mitral valve annulus along the PL from the anterior to posterior commissure (PC) at both ends of the basal portion of the anterior leaflet (AL) and reduces the normal size of the mitral valve annulus. We have used this method in all MVP cases ( Kanemoto et al ., 2001 , 2004 , 2010 , 2017c ) ( Fig. 5B ).…”
Section: Introductionmentioning
confidence: 96%
“…There have been a few reports of MVP performed in toy- and small-breed dogs ( Kanemoto et al ., 1990 , 1999 ; Boggs et al ., 1996 ) and some recent reports of MVP performed in small and medium-sized dogs ( Kanemoto et al ., 2001 , 2004 , 2010 ; Griffiths et al ., 2004 ; Uechi, 2012 ; Uechi et al ., 2012 ). However, we reported cases of long-term survival in small-breed dogs, one alive for 9 years and 1 month and another for 7 years and 10 months after MVP at 10 years of age ( Kanemoto et al ., 2017c ). At present, we are performing MVP for all MR cases, including cases with severe MR, which was previously considered an indication for MVR.…”
Section: Introductionmentioning
confidence: 99%